The small remnant liver after major liver resection - Yigitler, Cengizhan (2003)
The maximum extent of hepatic resection compatible with a safe postoperative outcome is unknown. The study goal was to determine the incidence and impact of a small remnant liver volume after major liver resection in patients with normal liver parenchyma. Among 265 major hepatectomies performed at our institution (1998 to 2000), 138 patients with normal liver and a remnant liver volume (RLV) systematically calculated from the ratio of RLV to functional liver volume (FLV) were studied. Patients were divided into five groups based on RLV-FLV ratio from ≤30% to ≥60%. Kinetics of postoperative liver function tests were correlated with RLV. Postoperative complications were stratified by RLV-FLV ratios. Ninety patients (65%) underwent resection of up to four Couinaud segments. The RLV-FLV ratio was ≤60% in 94 patients (68%) including only 13 (9%) with RLV-FLV ≤30%. There was no linear correlation between the number of resected segments and the RLV-FLV. Postoperative serum bilirubin but not prothrombin time correlated with extent of resection. The incidence of complications including liver failure was not different among groups. Analysis of the four groups with a RLV-FLV ratio <60% showed a trend toward more complications and a longer intensive care unit stay in patients with the smallest RLVs. After major hepatectomy in patients with normal livers, the proportion of patients with a small remnant liver is low and not directly related to the number of segments resected. Although the rate of postoperative complications, including liver failure, did not directly correlate with the volume of remaining liver, the postoperative course was more difficult for patients with smaller remnants. Therefore preoperative portal vein embolization should be considered in patients who will undergo extended liver resection who have (1) injured liver or (2) normal liver when the planned procedure will be complex or when the anticipated RLV-FLV will be <30%. (Liver Transpl 2003;9:S18-S25.)